2024
DOI: 10.1038/s41598-024-51665-9
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of influenza vaccination implicates regulation of RIG-I signaling by DNA methylation

Hongxiang Fu,
Harry Pickering,
Liudmilla Rubbi
et al.

Abstract: Influenza virus infection alters the promoter DNA methylation of key immune response-related genes, including type-1 interferons and proinflammatory cytokines. However, less is known about the effect of the influenza vaccine on the epigenome. We utilized a targeted DNA methylation approach to study the longitudinal effects (day 0 pre-vaccination and day 28 post-vaccination) on influenza vaccination responses in peripheral blood mononuclear cells. We found that baseline, pre-vaccination methylation profiles are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…In order to fully understand the host influences on vaccination and the ever-changing influenza variants over time, samples from these cohorts have been analyzed for host RNA gene expression profiles by transcriptomics [ 59 ], host glycomics [ 60 ], proteomics [ 61 ], and metabolomics [ 62 ], as well as DNA methylation and immune senescence [ 63 ]. These data sets have been used to develop predictive models of host responses and vaccine effectiveness [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to fully understand the host influences on vaccination and the ever-changing influenza variants over time, samples from these cohorts have been analyzed for host RNA gene expression profiles by transcriptomics [ 59 ], host glycomics [ 60 ], proteomics [ 61 ], and metabolomics [ 62 ], as well as DNA methylation and immune senescence [ 63 ]. These data sets have been used to develop predictive models of host responses and vaccine effectiveness [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of CD4 + T cells this signifies skewing from a Th1 inflammatory response to a Th2 noninflammatory response. Another recent study concerning the flu vaccine studied DNA methylation patterns in a longitudinal analysis of yearly vaccinations [127]. In this study it was found that repeated vaccinations lead to DNA methylation primarily of genes associated with the signaling pathway for the pattern recognition receptor RIG-1, retinoic-acid-inducible gene-1.…”
Section: H Imprinting and Vaccine Boostingmentioning
confidence: 94%
“…The outcome of increased RIG-1 activity was an increase in transcription of type 1 IFNs (α/ß). Analysis of the cells associated with the repeated flu vaccinations has shown that mast cells are involved in some way [127]. A ligand for RIG-1 is 5' ppp-dsRNA and it has been found that incorporation of this ligand, as an adjuvant, with a flu vaccine markedly increased the generation of neutralizing high affinity antibodies in mice [128].…”
Section: H Imprinting and Vaccine Boostingmentioning
confidence: 99%
“…In terms of CD4 + T cells, this signifies skewing from a Th1 inflammatory response to a Th2 noninflammatory response. Another recent study concerning the flu vaccine studied DNA methylation patterns in a longitudinal analysis of yearly vaccinations [ 126 ]. In this study, it was found that repeated vaccinations lead to DNA methylation, primarily of genes associated with the signaling pathway for the pattern recognition receptor RIG-1, retinoic-acid-inducible gene-1.…”
Section: Infection Vs Vaccination and Immune Responsementioning
confidence: 99%
“…The outcome of increased RIG-1 activity was an increase in transcription of type 1 IFNs (α/ß). Analysis of the cells associated with the repeated flu vaccinations has shown that mast cells are involved in some way [ 126 ]. A ligand for RIG-1 is 5’ ppp-dsRNA, and it has been found that incorporation of this ligand, as an adjuvant, with a flu vaccine markedly increased the generation of neutralizing high affinity antibodies in mice [ 127 ].…”
Section: Infection Vs Vaccination and Immune Responsementioning
confidence: 99%